Linguistic Characteristics and Interpretation Strategy Based on EVS Analysis of Korean-Chinese, Korean-Japanese Interpretation - Kim, Hye-Rim (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis study was stimulated by several questions: What time lag is contained in the synchronicity of simultaneous interpretation? How do the linguistic characteristics of the language to be interpreted influence synchronicity? And in what is the interpreter’s strategy for achieving synchronicity in interpretation from Korean to other languages? To answer these questions, EVS measurements of Korean-Japanese and Korean-Chinese interpretation materials were analyzed. The results showed that in Korean-Chinese interpretation the interpreter begins the interpretation before a whole sentence is finished, and that in Korean-Japanese interpretation, the interpreter leaves a time lag before beginning the interpreted utterance. This study indicated that the information processing in simultaneous interpretation is not carried out through the characteristics of the language itself but the interpreter’s guessing based on unit of meaning and strategies accumulated by the interpreter through long experience.